Defining the biomechanical properties of the rabbit trachea. (10th June 2014) - Jones, Matthew C.; Rueggeberg, Frederick A.; Faircloth, Hunter A.; Cunningham, Aaron J.; Bush, Carrie M.; Prosser, John D.; Waller, Jennifer L.; Postma, Gregory N.; Weinberger, Paul M.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Surgical advancements rely heavily on validated animal models. The New Zealand White (NZW) rabbit is a widely used model for airway research, including regenerative medicine applications. Currently, the biomechanical properties of the normal rabbit trachea are not known. Our objective was to define these properties to assist in the standardization and understanding of future airway research using this model. Study Design Laboratory‐based study. Methods Fresh tracheas from four adult NZW rabbits were dissected into 20 segments. To examine the biomechanical properties, segments were subjected to uniaxial tension (n = 9) and compression (n = 11) testing. Yield and maximum load (tension) and force at 50% displacement (compression) were recorded, and differences between segments were examined using analysis of covariance. Results Normative data for native rabbit trachea show mean maximum load = 6.44 newtons (N), yield load = 5.93 N, and compressive strength = 2.10 N. In addition to establishing the baseline measurements, statistically significant differences in tensile measures based on location along the trachea and diameter were identified. Proximal segments had significantly higher maximum load (P = .0029) and yield load (P = .0062) than distal segments. Association between diameter and both maximum load (P = .0139) and yield load (P = .0082) was observed. Conclusions The adult NZW rabbit trachea is intrinsically less able to withstand tensile and compressive forces, compared to other airway models such as sheep or cadaveric human. Establishment of normative values will enable future research into changes in tracheal biomechanical properties during regenerative medicine manipulation and processing. Level of Evidence NA Laryngoscope 124:2352–2358, 2014